Pengembangan media pembelajaran Buku Komik Biologi pada Materi Sistem Pencernaan Manusia untuk Siswa SMP - Arifah Novia Arifin; Arsad Bahri; Muhiddin Palennari; Chaidir Anas (Seminar Nasional LP2M UNM, 2019)
This Research and Development (R and D) concerns on Alternative learning media development regarding comic book biologyfor Human Digestive system subject. The R and D’s model used Analyze, Design, Develop, Implement, Evaluate (ADDIE). Validity test obtained from two expert validators and Practicality test obtained from the using of media by teacher and students. The Develop stage of this study conducted by validating comic book for further be implemented on SMP Negeri 1 Tinggimoncong, Class of VIIIA. The number of subjects comprised of 32 students. Data collected from interview, observation and questionnaire. The result of validity test showed the average of media feasibility percentage is 92%. While the subject matter feasibility gained 87%. Both of these result showed very decent category which was meant that the media is feasible to be used. The average of teacher and students respond gained 85% and 87% respectively toward positive respond. From the point of feasibility which had been evaluated by validity and practical test, this study can be conclude that comic book is valid and practice learning media to be implemented in learning process.